2013
DOI: 10.1038/mp.2013.130
|View full text |Cite
|
Sign up to set email alerts
|

Lanicemine: a low-trapping NMDA channel blocker produces sustained antidepressant efficacy with minimal psychotomimetic adverse effects

Abstract: Ketamine, an N-methyl-D-aspartate receptor (NMDAR) channel blocker, has been found to induce rapid and robust antidepressant-like effects in rodent models and in treatment-refractory depressed patients. However, the marked acute psychological side effects of ketamine complicate the interpretation of both preclinical and clinical data. Moreover, the lack of controlled data demonstrating the ability of ketamine to sustain the antidepressant response with repeated administration leaves the potential clinical util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
184
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(194 citation statements)
references
References 32 publications
8
184
1
1
Order By: Relevance
“…Indeed, preliminary studies evaluating the antidepressant potential of i.v. infusions of AZD6765 appear consistent with this hypothesis, as AZD6765 showed low potential for dissociative effects, psychotomimetic effects, or cognitive impairment at doses of 100 and 150 mg in patients (Sanacora et al, 2014;Zarate et al, 2013). In the present studies acute treatment with AZD6765 did not impair list-DMS performance at doses of 1 and 3 mg/ kg, achieving plasma drug concentrations of 1 μM-656 nM and 3.7-4.2 μM, respectively, during the testing period.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Indeed, preliminary studies evaluating the antidepressant potential of i.v. infusions of AZD6765 appear consistent with this hypothesis, as AZD6765 showed low potential for dissociative effects, psychotomimetic effects, or cognitive impairment at doses of 100 and 150 mg in patients (Sanacora et al, 2014;Zarate et al, 2013). In the present studies acute treatment with AZD6765 did not impair list-DMS performance at doses of 1 and 3 mg/ kg, achieving plasma drug concentrations of 1 μM-656 nM and 3.7-4.2 μM, respectively, during the testing period.…”
Section: Discussionsupporting
confidence: 75%
“…Preclinical studies have shown that AZD6765 is a modest potency, voltage-dependent, nonselective, NMDA receptor channel blocker (Sanacora et al, 2014). Although this profile is similar to ketamine, the 'low trapping' effects seen in electrophysiology assays are hypothesized to better preserve use-dependent block under conditions of normal synaptic transmission, leading to improved tolerability (Mealing et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results also raise further questions regarding the relationship of changes in gamma power to psychotomimetic effects. Recent studies of the low-trapping NMDA channel blocker lanicemine showed an enhanced gamma-band power both in rats and humans, but it did not induce psychotomimetic effects in patients (Sanacora et al, 2014). On the other hand, in humans, CP-101,606 was observed to evoke dissociative effects in some patients at higher doses (Nutt et al, 2008;Preskorn et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…AZD6765 had lower response rates, lower remission rates, and a shorter duration of effect . In a subsequent 3-week, placebo-controlled trial, patients with TRD received repeated adjunctive AZD6765 (now renamed lanicemine) infusions at two doses (100 and 150 mg); as hypothesized lanicemine had antidepressant efficacy without ketamine-like side effects [Sanacora et al 2014b]. However, as presented at the 2014 American Society of Clinical Psychopharmacology annual meeting in Hollywood, FL, in a 6-week phase IIb study, adjunctive repeated-dose (50 and 150 mg) AZD6765/lanicemine failed to separate from placebo, potentially due to the large placebo effect (39% placebo response rate at trial end) [Sanacora et al 2014a].…”
Section: Peripheral Measuresmentioning
confidence: 99%